Proximate Composition, Phytochemicals, Phenolic Compounds, and Bioactive Characterization of Mauritia flexuosa L.f. Seeds - Claudia Cristina Pérez Jaramillo; Liceth N. Cuéllar Álvarez; Walter Murillo Arango (Plants)
Mauritia flexuosa, commonly known as “canangucha,” holds significant nutritional and economic value in the Amazon region. While its pulp is widely utilized in local food products, the seed or kernel is largely underutilized. This study investigated the proximal and phytochemical composition of M. flexuosa, alongside its biological properties, specifically focusing on the hypoglycemic activity of an ethanolic extract from M. flexuosa seeds (MFSs). Proximal analysis revealed that MFSs are a notable source of crude fiber (28.4%) and a moderate source of protein (9.1%). Phytochemical screening indicated a high total polyphenol content (123.4 mg gallic acid equivalents/100 mg dry weight) and substantial antiradical capacity against the ABTS radical (IC50 = 171.86 µg/mL). Notably, MFS ethanolic extracts exhibited significant in vitro antihyperglycemic activity via inhibiting α-amylase and α-glucosidase enzymes, demonstrating comparable inhibition to acarbose at higher concentrations. This hypoglycemic effect was further corroborated in an in vivo rat model with induced diabetes, where the administration of 100 mg/kg of MFS ethanolic extract significantly reduced blood glucose levels compared to the diabetic control group (p < 0.05). A moderate antihypertensive effect was observed at a concentration of 150 mg/kg, correlating with ACE inhibition. High-performance liquid chromatography–mass spectrometry (UHPLC-ESI-HRMS) analysis of the seed extract identified phenolic compounds including ellagic, p-coumaric, and chlorogenic acids, as well as flavonoids such as quercetin, myricetin, and epicatechin. This study provides the first evidence of the hypoglycemic activity of MFSs, offering valuable insights into their phytochemistry and potential therapeutic applications.